Sustainable development in a construction related curriculum – quantity surveying students’ perspective - Tan, Amelia; Udeaja, Chika; Babatunde, Solomon Olusola; Ekundayo, Damilola (International Journal of Strategic Property Management, 2017)
Higher education institutions (HeIs) across the globe are increasingly aware of the need to integrate sustainability education within the curricula. this triggered a number of studies were conducted by earlier researchers in embedding sustainability education within the curricula. thus, studies have been carried out to evaluate how students perceived sustainable development in their curricula, particularly in engineering and other related courses. few of these studies were conducted in built environment, most especially in quantity surveying. It is against this backdrop that necessitated this study. the purpose of this study is to establish the extent in which sustainable development is embedded in the construction related curriculum using the perception of quantity surveying students. the study adopted literature review, documentary reports among others as a secondary method of data collection. Primary data were collected through online questionnaire survey administered to 330 randomly selected quantity surveying students in a university in the uK. out of which 87 completed questionnaires were retrieved and suitable for the analysis. the quantitative data obtained were analysed using mean score, one-way analysis of variance (anoVa) and regression analysis. the study identified 46 sustainability topics, which were grouped into 6 categories (i.e. A–F). Based on these categories, the study found that students’ knowledge level on sustainability was a little above ‘basic/ limited knowledge with the overall mean score value of 2.38 on a 4 – point likert scale. the study further revealed that the students placed high importance on sustainability education, despite their knowledge level were found lower. The study findings would be used to establish the extent of sustainability within the curriculum in the quantity surveying programme. also, this study would be of great value to academic staff and university management boards to develop a framework for incorporating sustainability education in the curriculum.